Perceived Influence of Socio-Economic Infrastructure on Vocational Skills Acquisition and Practice Among Youths in Bonny Local Government Area - A.U. Nnodim; Matilda T. Allison (International Journal of Education, Teaching, and Social Sciences, 2021)
The study was conducted to investigate the perceived influence of socio-economic infrastructure on vocational skills acquisition and practice among rural youths in Bonny Local Government Area, Rivers State. Three objectives, three research questions and three hypotheses guided the study. The total population of the study was 78,373 rural youths while the sample size was 398 youths sampled from the population using Taro Yeman sample determination model. A structured questionnaire was used to gather data for the study. Data were analyzed using mean and standard deviation , while z-test was used to test the hypotheses at 0.05 level of significance. The findings revealed that youths in Bonny Local Government Area agreed that they were exposed to varied vocational skills training . Also, the respondents agreed that transportation influences their acquisition and practice of vocational skills, and finally, the youths agreed that electricity influences their vocational skills acquisition and practice amongst other. It was then recommended that government should provide more training centres for youths, employment should not be on paper and pen qualifications alone but also on skills acquisition related to the job areas.